“Efectividad de la cirugía funcional endoscópica de senos paranasales en la rinosinusitis crónica del Hospital Nacional Almanzor Aguinaga Asenjo. 2017” - Gutierrez Montoya, Maria de Fatima (2019)
ABSTRACT The objective of this research was to determine the effectiveness of the Endoscopic Functional Surgery of the Paranasal Sinuses in patients with Chronic Rhinosinusitis of the Otorhinolaryngology Service of the Almanzor Aguinaga Asenjo National Hospital in 2017. The research was observational, cross-sectional and prospective in a sample of 70 patients . In patients undergoing endoscopic functional surgery during the course of twelve months of follow-up, 11.4% presented recurrence, being more frequent after the fifth decade of life, affecting both sexes equally. 92.9% improved symptoms without significant statistical differences according to age and sex. The entire population included in the study fulfilled the period of days of physical disability of the norm for ESSALUD (18 days) and the average time of hospital stay was 2 + 0.7 days, without significant statistical difference between sexes. Endoscopic surgical treatment was found to be effective in nine out of ten patients due to: lower recurrence, greater percentage of symptom improvement, days of non-prolonged physical disability and fewer days of hospital stay.